2012
DOI: 10.1002/dneu.22047
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal repetitive needle pricking: Plasticity of the spinal nociceptive circuit and extended postoperative pain in later life

Abstract: Repetitive exposure of neonates to noxious events is inherent to their health status monitoring in neonatal intensive care units (NICU). Altered basal nociception in the absence of an injury in later life has been demonstrated in ex-NICU children, but the impact on pain hypersensitivity following an injury in later life is unknown. Also, underlying mechanisms for such long-term changes are relatively unknown. The objective of this study is to investigate acute and long-term effects of neonatal repetitive painf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 48 publications
8
69
0
1
Order By: Relevance
“…Rodent studies of long-term effects of early pain on pain thresholds have shown hyper- and hypo- sensitivity, depending on the nature of the pain stimulus [7,8]. Consistent with these animal findings, human studies comparing preterm and full-term children show that the direction of pain responses depends on duration and type of stimulus.…”
Section: Introductionmentioning
confidence: 78%
“…Rodent studies of long-term effects of early pain on pain thresholds have shown hyper- and hypo- sensitivity, depending on the nature of the pain stimulus [7,8]. Consistent with these animal findings, human studies comparing preterm and full-term children show that the direction of pain responses depends on duration and type of stimulus.…”
Section: Introductionmentioning
confidence: 78%
“…Methodological differences may account for these findings, inflammatory pain or pain from injections may not have the same consequences as needle-pricks. We question the invasiveness of our needle-prick pain stimulus, given that we used very thin needles (30G) and did not penetrate deeper layers, such as tendon or bone, in contrast to the apparently more invasive procedures used in needle-prick pain in previous rat studies [1,27,41]. It should be noted that we undertook interventions 10 times daily for six days, based on the median exposure to painful procedures during NICU care [54].…”
Section: 0 Discussionmentioning
confidence: 99%
“…Plantar hind paw incision was performed at the age of 8 weeks, a young-adult age at which alterations in the nociceptive network organization and in hind paw incision pain have been evidenced following neonatal pain exposure [41]. After baseline nociceptive and locomotor activity testing, all male offspring received an injury to the left hind paw, i.e.…”
Section: Methodsmentioning
confidence: 99%